Magnetschnellbahn: Vision oder Fiktion. Die Fallstudie "SWISSMETRO". - Weidmann, Ulrich (Deutscher Verkehrs-Verl., 2008)
Seit über 40 Jahren steigen die Geschwindigkeiten der konventionellen Bahn. Innerhalb der EU soll langfristig ein erfolgreiches Hochgeschwindigkeitsnetz entstehen. Gleichzeitig werden neue noch schnellere Verkehrssysteme entwickelt, welche sich aber bisher nicht durchsetzen konnten. Die ETH Zürich geht den Gründen für den bisherigen Misserfolg am Beispiel der Swissmetro nach. difu

Track-guided operating systems facilitate high speed service. For more than four decades, conventional railways have been upgraded for high speed operations while also completely new systems have been developed. In the first case, this has led to the creation of a successful high speed rail network that has become an integral part of EU transport policy. In the second case, new rail systems have achieved a high technical standard yet have not, apart from a few instances, managed to achieve the hoped-for breakthrough. A case study of the ETH Zürich evaluates the reasons for this apparent lack of success, using the example of the Swissmetro project and assessing its future chances across Europe. The conclusion drawn is that there is no market for new rail systems of this nature, even on a long term basis. difu
Keywords: Verkehr; Eisenbahn; Verkehrstechnologie; Hochleistungsschnellbahn; Verkehrsplanung; Verkehrssystem; Verkehrsnetz; Verkehrsnachfrage; Magnetbahn; Reisezeit; Verkehrsangebot; Fallstudie